Characterizing and Modelling of Indoor Radio Propagation Channel at ISM Band - Abdallah, Abdulkareem S.; Ezzeldin, Vessar (Basrah Journal for Engineering Sciences, 2006)
The investigation of the indoor electromagnetic propagation has been performed at the unlicensed industrial, scientific, and medical (ISM) band, which has gained increased attention recently due to high data rate communication systems developed to operate in it. The effect of the incidence angle and materials thicknesses on the reflection coefficients for both horizontal and vertical polarization has been studied. Two-dimensional ray-tracing model has been suggested to simulate the influence of buildings electromagnetic properties on indoor radio channel characteristics, such as signal level, rms delay spread, and coherence bandwidth. Results show that the influence of the permittivity is more important than the influence of the order of reflection considered for the ray- tracing model. It is also shown that, compared with power level, rms delay spread is more sensitive to the building dielectric parameters. Maximum rms delay spread is dependent mainly on the reflectivity of the walls which dependent on the dielectric parameters.